Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ma12233919
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Characterization of Non-Uniform Corrosion of Steel Bars in Concrete Beams after Accelerated depassivation and Seven-Year Natural Corrosion

Abstract: In this work, the non-uniform corrosion characteristics of steel bars in stressed reinforced concrete beams after accelerated depassivation and seven-year outdoor natural corrosion is analyzed using fractal theory. 3D laser scanning and 3D reconstruction technology are applied to collect the cross-sectional area along the steel bars and obtain the corrosion curves. The non-uniformity of corrosion is analyzed by fractal dimensions which is calculated by variation method. The results indicate that the initial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The residual cross-sectional area reflecting the multi-dimensional corrosion loss on the whole circumference is more comprehensive than the corrosion depth and more straightforward than other corrosion indices [ 28 ]. To better understand the longitudinal corrosion distribution of steel rebars, Figure 5 shows the residual cross-sectional areas along the length of steel rebars with different corrosion levels within the parallel length.…”
Section: Corrosion Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual cross-sectional area reflecting the multi-dimensional corrosion loss on the whole circumference is more comprehensive than the corrosion depth and more straightforward than other corrosion indices [ 28 ]. To better understand the longitudinal corrosion distribution of steel rebars, Figure 5 shows the residual cross-sectional areas along the length of steel rebars with different corrosion levels within the parallel length.…”
Section: Corrosion Characteristicsmentioning
confidence: 99%
“…Absolutely uniform corrosion is an ideal state that hardly exists in engineering. It is often observed that corrosion on the rebar surface is longitudinally and circumferentially non-uniform [ 28 , 29 ]. Furthermore, corrosion patterns influence the tensile properties of corroded rebars [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the concrete members in the sulfuric acid or hydrochloric acid corrosion environment [1][2][3][4][5][6]. Several investigations indicated that acid corrosion had become one of the major threats affecting the mechanical properties of RC structures [7][8][9][10][11][12], resulting in the reduction of bearing capacity and ductility. Meanwhile, the double coupling actions of acid corrosion and load not only affected the durability of concrete structures but also made the calculation method used in the existing design no longer applicable to the concrete severely corroded by acid, endangering the safety of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion of steel is the major cause of deterioration in the serviceability and sustainability of reinforced concrete (RC) structures, especially for those in the chloride-laden environment [1][2][3]. As steel corrosion propagates, the volumetric expansion due to rust formation generates expansive pressure on the surrounding concrete and eventually leads to cracking and peeling-off of concrete cover [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%